ANALISIS BALANCED SCORECARD PADA PERENCANAAN SISTEM INFORMASI SEKOLAH MUSIK - Andrijana Kusuma, Kanggep; Prama Agusmar Yahya, Angga; Naufal, Alman; Ratna Juwita Sari, Deassy; Yudi Permana, Nana (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
Balanced Scorecard analysis in music school system planning can help company strategy to compete in music school business. Where it is designed to run strategy into goals, measures, targets, and strategic initiatives. Also as a group that interacts and depends on each other regularly forms a unity and helps music schools to effectively run their strategy. The research conducted aims to visualize the company's strategy, communicate various strategic goals, align and make plans and set goals, improve Reciprocal effects and learning. In this study, the author conducted observations at a music school to obtain data, documents, and also conducted interviews with the owner of the music school as a source of information needed by the author. The final results of this study consist of several perspectives, namely financial perspective, customer perspective, internal business process perspective and learning and growth perspective. Balanced scorecard analysis within the scope of the music school business will be very helpful in achieving customer satisfaction, market share, facilitating infrastructure and creating an initiative workforce. The suggestion from this study is that the results of the balanced scorecard are expected to contribute to running a business strategy into goals, targets, measures and strategic initiatives. Which will greatly influence the achievement of the goals of the music school. Also supports the company in implementing Information Systems and Information Technology planning.